The Stereotypical Gag in Carlo Emilio Gadda’s and Pietro Germi’s Detective Stories - Santi, Mara; Nemegeer, Guylian (Quaderni d'Italianistica)

(untitled) (Iter Press, 2021)
This article analyzes two comic incidents portrayed in Gadda’s That Awful Mess on the Via Merulana and its adaptation The Facts of Murder by Pietro Germi. We argue that the inclusion of what we term ‘stereotypical gags’ in the detective novel functions as a modernist device that brings about a distancing of the audience and acts to distort the boundaries of genre. We show how the stereotypical gag both foregrounds and backgrounds the authorial humorous agency and results in satire and parody, respectively. In the first case, the authorial agency explicitly endorses humorous clichés and mocks along with the audience’s societal conventions. In the second case, humour generates a less obvious incongruity with respect to the discourse of the genre, resulting in parody through which the authorial agency mocks the audience and its trust in the values of the traditional detective story.